Experimental and Theoretical Study on the False Positive of Monomethyltin Determination in Toys Based on Gastric Juice Migration - Lina Huang; Hanke Li; Yuhang Li; Peng Ren; Lezhou Yi; Yang Chen; Tongmei Ma (International Journal of Analytical Chemistry)
Background. Organic tin compounds (OTCs), a group of high-risk hazardous substances, are highly concerned in safety regulation of consumer products especially for toys because they can cause serious damage to organs after prolonged or repeated exposure. Gastric juice migration is nowadays widely implemented to assess organic tin intake from toys or food-contact materials; however, the followed up detection method using sodium tetraethylborate [NaB(Et4)] as a derivatization agent may directly lead to false positive of monomethyltins (MMT). Objective. In order to avoid the phenomena of false positive of MMT in the course of laboratory testing of toys, it is necessary and important to perform relative experimental and theoretical studies to reveal the cause of false positive of MMT. Method. With metal tin powder as a representative of inorganic tin which existed in real samples, it was treated with artificial gastric juice (0.07 mol/L·HCl), followed by ethyl derivatization using sodium tetraethylborate [NaB(Et)4] and then analyzed by gas chromatography-mass spectrometry (GC-MS) according to the procedure specified in the standard of EN 71-3:2013+A3:2018 issued by the European Committee for Standardization (CEN). Results. Without any OTCs in the starting materials, MMT false positive can be reproduced by detecting 0.56 mg/L of triethylmethyltin (TEMT) together with approximately 1000 mg/L of tetraethyltin (TeET), which is similar to real samples. Further, it is demonstrated that the detected amount of TEMT is linearly related with the added amount of NaB(Et)4, and that the formation of TEMT (methyl derivative) is easier than TeET (ethyl derivative) even though the ethyl group is present in a larger amount than the methyl group. Conclusions. The phenomena of MMT false positive which occurred in the laboratory testing of toys is mainly because that TEMT is highly likely to be obtained from the reaction of inorganic tin and trace level of methylation agent impurities contained in the derivatization reagent—NaB(Et)4. To avoid MMT false positive, it is concluded that the maximum acceptable mole ratio of methylation agent impurities contained in NaB(Et)4 is approximately 0.028%. This research is helpful to be aware of methylation impurities and is favorable to avoid false judgment caused by MMT false positive in routine analysis of toys.